Profitability of property industries in Indonesia by using firm specific factors and macroeconomic factor - pandu adi cakranegara (JAAF (Journal of Applied Accounting and Finance), 2022)
Property companies are a growing industry in Indonesia. This trend makes the property industry an economically attractive industry for the investor. Due to that development, this study examines the factors that affect the profitability of property companies. This study's profitability is represented by the Return On Equity ratio chosen because this variable will provide returns to equity investors. The independent variables in this study consist of company-specific variables and macroeconomic variables. The research method used is the multiple linear regression method using secondary data taken from the company's financial statements from 2015 to 2019. The findings of this study are that both company-specific and macroeconomic factors significantly influence the profitability of property companies. Specifically, company-specific factors that have a significant effect on profitability are also affected by macroeconomic factors, such as companies' ability to owe as represented by the ratio of Debt to Equity Ratio. Investors can use the findings from this study to determine which companies are suitable for investment. Meanwhile, from the company side, management can focus on this study's findings to increase the company's profitability.